Improving accessibility of trust guidelines and protocols at the Great Western Hospital, Swindon. Issue 1 (10th December 2014) - Robertson, Ian; Smith, Abigail; Tucker, Jennifer; Cilia, Erica; Chen, Kangni; Marion, Rose; Nesbitt, Julian; Ramcharitar, Steve; Cathiavadi Greamspet, Mala
Abstract: Trust guidelines and policies outline recommendations for the management of common clinical and non-clinical situations, serving to standardise best practice. Prior to this project, there was no consolidated location for these documents. Lack of organisational structure and inadequate search functionality within the trust intranet led to time wasted locating information, acting outside of recognised best practice, and ultimately potentially compromising patient safety. We surveyed 55 junior doctors, 95% of respondents were dependent on guidelines on a daily basis. 20% spending greater than 5 minutes to locate protocols and 38% unable to locate some relevant documents at all. We analysed the time taken for junior doctors to locate six randomly selected protocols. Pre-intervention mean time was 133 seconds (on six occasions doctors were unable to locate the guideline). All trust guidelines and protocols currently available on the intranet were collated, consolidated, and renamed according to content. These were then re-alphabetised and new search terms linked to each document. Existing links were then uploaded and a single web page made available via the trust intranet homepage. The new page was publicised by email, posters and interdepartmental presentations. In our post intervention survey, 97% of respondents were aware of the project and had made use of the page. All protocols were located during re-testing with 90% of those resurveyed stating it was easier to locate protocols. Overall, a reduction in the time and number of clicks required to locate protocols was demonstrated: mean time 16 seconds vs 133 seconds pre-intervention (n=60). 53% of guidelines located in <30s and 86% <2 minutes.